KAJIAN PEMBUATAN BERAS ANALOG BERBASIS TEPUNG UMBI DALUGA (Cyrtosperma merkusii (Hassk) Schott) - Ronal Lumba; Christine F. Mamuaja; Gregoria S. S. Djarkasi; Maria F. Sumual (COCOS, 2013)
ABSTRACTDaluga (Cyrtosperma merkusii Hassk) Schott is one type of plant tubers that have a highcarbohydrate content, but its use is limited because of limited tecnohologi owned by the public.Analog Rice is one of the solutions can be developed either in terms of the use of a new food source orto diversify food. The research objective is to get the right concentration of CMC in the manufactureof analog rice flour daluga bulbs. The first phase of the treatment of the old flour soaking slicedtubers daluga the pristine 1 % NaCl solution for 60 and 120 minutes. Further analysis of oxalic acid,oxalic acid treatment followed pads low second stage of rice manufacturing are analog to thetreatment CMC concentration addition. Treatment A = (100% flour daluga : 0% CMC), B = (99.6%flour daluga : 0.4% CMC), C = (99.2% flour daluga: 0.8% CMC), D = (98.8% flour daluga : CMC1.2%), E = (98.4% flour daluga : 1.6% CMC). Organoleptic test results, treatment was continuedwith an analysis of selected physical and chemical properties. Results for flour daluga an average of0.35-0.52% oxalic acid content and chemical composition of the water content of 11.97%, ash contentof 2.4%, 0.89% fat content, protein content 1.11% and carbohydrates conten of 83, 65. Analog Forrice, the chosen treatment CMC concentrations are treatment B = (99.6% flour daluga: 0.4% CMC).nalisis With the results of physical and chemical properties of the analog rice yield 53.52%, colorsrice 70% , 43%, 179.96% water absorption, rehydration time of 7 minutes, water content 7.88%, ashcontent of 2.6%, 5.42% fat content, protein content 0.66%, and carbohydrates conten of 83, 44%.Keywords: Bulbs daluga, oksalate, analog rice, food security